2013
DOI: 10.1038/nrendo.2013.96
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs—mediators of myometrial contractility during pregnancy and labour

Abstract: The maintenance of myometrial quiescence and initiation of contractility, which lead to parturition at term and preterm, involve a shifting equilibrium between anti-inflammatory and proinflammatory signalling pathways. Progesterone (P4), acting through the progesterone receptor (PR), has an essential and multifaceted role in the maintenance of myometrial quiescence. This effect of P4-PR signalling is mediated, in part, by its anti-inflammatory actions and capacity to repress the expression of genes that encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 121 publications
3
36
0
4
Order By: Relevance
“…Members of the miR-199a/214 cluster are positively regulated by ZEB1 and are down-regulated in the uterus during parturition, allowing the up-regulation of their target, cyclooxygenase-2 (COX-2) (31). Similar changes in these miRNAs occur with the induction of preterm labor in mice by the PR antagonist RU486 or lipopolysaccharide (LPS), and in term myometrium of women in labor (32). Together, these data shed light on the opposing roles of miRNA clusters in the transition from uterine quiescence to a contractile phenotype and imply a central role for ZEB proteins in this process.…”
Section: Established Pathways Implicated In Term and Preterm Parturitionmentioning
confidence: 65%
“…Members of the miR-199a/214 cluster are positively regulated by ZEB1 and are down-regulated in the uterus during parturition, allowing the up-regulation of their target, cyclooxygenase-2 (COX-2) (31). Similar changes in these miRNAs occur with the induction of preterm labor in mice by the PR antagonist RU486 or lipopolysaccharide (LPS), and in term myometrium of women in labor (32). Together, these data shed light on the opposing roles of miRNA clusters in the transition from uterine quiescence to a contractile phenotype and imply a central role for ZEB proteins in this process.…”
Section: Established Pathways Implicated In Term and Preterm Parturitionmentioning
confidence: 65%
“…Studies of myometrium have traditionally been limited to the pregnant uterus and labor [10], although myometrial contractions felt as menstrual period associated 'cramps' are a symptom that is commonly reported by women during menstruation. This dramatic increase in the amplitude (labor like, and increased from a base line of <30 mmHg up to 50-200 mmHg) of myometrial contractility, particularly seen in the inner subendometrial zone of the myometrium during menstruation, is likely to be induced by increased endometrial production of prostaglandins such as PGF 2α and PGE 2 [11,12].…”
Section: Normal Menstruationmentioning
confidence: 99%
“…The shedding of the 'old' stratum functionalis usually happens over 1-2 days yet the menstrual bleeding continues during the proliferation and repair of the surface epithelium of the damaged stratum functionalis which takes several days. The endometrial hemostasis which is responsible for cessation of menstrual bleeding involves platelet aggregation, fibrin deposition and thrombus formation [9].Studies of myometrium have traditionally been limited to the pregnant uterus and labor [10], although myometrial contractions felt as menstrual period associated 'cramps' are a symptom that is commonly reported by women during menstruation. This dramatic increase in the amplitude (labor like, and increased from a base line of <30 mmHg up to 50-200 mmHg) of myometrial contractility, particularly seen in the inner subendometrial zone of the myometrium during menstruation, is likely to be induced by increased endometrial production of prostaglandins such as PGF 2α and PGE 2 [11,12].…”
mentioning
confidence: 99%
“…Moreover, in recent studies, we observed that P 4 /PR increases expression of the transcriptional inhibitor, ZEB1, which binds to the promoters of the contractile genes CX43 and OXTR to suppress their expression throughout most of pregnancy ( Fig. 1) (Renthal et al 2010(Renthal et al , 2013. P 4 /PR Maintains Myometrial Quiescence by Its Anti-Inflammatory Actions P 4 /PR maintains uterine quiescence, in part, by inhibiting activation of inflammatory response pathways and expression of "contractile" genes within the uterus and cervix and by blocking the production of chemokines that promote chemotaxis of immune cells.…”
Section: Mechanisms For P 4 /Pr Regulation Of Myometrial Quiescencementioning
confidence: 89%